Para-Selective C–H Borylation of Common Arene Building Blocks Enabled by Ion-Pairing with a Bulky Countercation - Mihai, Madalina T. (J Am Chem Soc, 2019)
[Image: see text] The selective functionalization of C–H bonds at the arene para position is highly challenging using transition metal catalysis. Iridium-catalyzed borylation has emerged as a leading technique for arene functionalization, but there are only a handful of strategies for para-selective borylation, which operate on specific substrate classes and use bespoke ligands or catalysts. We describe a remarkably general protocol which results in para-selectivity on some of the most common arene building blocks (anilines, benzylamines, phenols, benzyl alcohols) and uses standard borylation ligands. Our strategy hinges upon the facile conversion of the substrates into sulfate or sulfamate salts, wherein the anionic arene component is paired with a tetrabutylammonium cation. We hypothesize that the bulk of this cation disfavors meta-C–H borylation, thereby promoting the challenging para-selective reaction.